Environmental and Occupational Exposure to Chemical Agents and Health Challenges (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue focuses on the use of biomonitoring tools applied to human environmental and occupational chemical exposures, and on the toxicological characterization and modes of action of hazardous and its possible health effects. A better knowledge and understanding of toxicological aspects and respective effects at a molecular and cellular level, in parallel with the development and application of biomonitoring tools in exposome science, enables science-based decisions at regulatory toxicology.